A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed